2016
DOI: 10.5603/fhc.a2016.0015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and expression of SLC45A2 in the skin of sheep with different coat colors

Abstract: Introduction. To investigate whether the membrane-associated transporter protein SLC45A2 is differentially expressed in the skin of sheep with different coat colors and to determine its correlation with coat color establishment in sheep. Material and methods. The expression of SLC45A2 in sheep skin samples with different coat colors was qualitatively and quantitatively analyzed by PCR amplification, RT-PCR, immunohistochemical staining and Western blotting. Results. A 193-bp SLC45A2 CDS sequence was successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…In our study, the SLC45A2 gene was enriched in the cellular component, melanosome membrane; and in the two BP, melanin biosynthetic process and developmental pigmentation. The expression levels of the SLC45A2 gene were up-regulated in the cyan gray and black groups, which was consistent with studies in small-tailed Han sheep (Wang et al, 2016) and with the results of our RNA-seq analysis.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the SLC45A2 gene was enriched in the cellular component, melanosome membrane; and in the two BP, melanin biosynthetic process and developmental pigmentation. The expression levels of the SLC45A2 gene were up-regulated in the cyan gray and black groups, which was consistent with studies in small-tailed Han sheep (Wang et al, 2016) and with the results of our RNA-seq analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Skin pigmentation in animals is a polygenic trait, and may be influenced by different kinds of multi-gene interactions ( Barsh, 1996 ). The proteins and genes associated with skin color in humans, mice, chickens, and sheep include agouti signaling protein (ASIP) ( Lu et al, 1994 ), melanocyte-stimulating hormone receptor (MSH) ( Robbins & Nadeau, 1993 ), microphthalmia transcription factor (MITF) ( Dong, Yoshiaki & Vijayasaradhi, 2002 ; Vetrini et al, 2004 ; Wang et al, 2018 ), tyrosinase (TYR) ( Deng et al, 2008 ; Yu et al, 2017 ), tyrosinase-related protein-1 (TYRP1) ( Chun et al, 2016 ), dopachrome tautomerase (DCT) ( Xue et al, 2018 ), melanocortin 1 receptor (MC1R) ( Fontanesi et al, 2010 ; Bourgeois et al, 2016 ; Wolf Horrell, Boulanger & D’Orazio, 2016 ), solute carrier family 45 member 2 (SLC45A2) ( Wang et al, 2016 ), and others. There are over 100 known color loci in mice and many of them have been cloned and sequenced ( Bennett & Lamoreux, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have found that many growth factors and genes regulate melanogenesis. For example, we found that ocular albinism type 1 protein (OA1) and glycoprotein nonmetastatic melanoma protein b (GPNMB) regulate melanogenesis in mouse melanocytes; the expression of slc45a2 and endothelin 3 are also related to sheep coat colors [4][5][6][7]; cyclin-dependent kinase 5 could regulate melanogenesis and epidermal structures [8]; and FGF21 regulates the pigmentation of alpaca melanocytes by the ERK1/2 pathway [9]. Moreover, IGF1 can modulate alpaca melanogenesis by the cAMP pathway [10].…”
Section: Introductionmentioning
confidence: 99%